2019
DOI: 10.7759/cureus.5653
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Associated Factors of Parental Refusal to Perform Lumbar Puncture in Children with Suspected Central Nervous System Infection: A Cross-sectional Study

Abstract: ObjectiveLumbar puncture (LP) is a useful procedure which is performed for both diagnosis and treatment of numerous conditions affecting children and adults. The purpose of this study was to determine the frequency and cause of increased parental refusal to perform LP in the pediatric population.MethodA cross-sectional study was conducted from January 2018 to June 2019 at the Civil Hospital, Dow University of Health Sciences, pediatric department, Civil Hospital, Karachi. Over the 18-month time period, a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 15 publications
5
20
1
Order By: Relevance
“…Several other studies support our findings [1][2][3][4]. Our literature search revealed that parental LP refusal is significantly associated with LAMA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several other studies support our findings [1][2][3][4]. Our literature search revealed that parental LP refusal is significantly associated with LAMA.…”
Section: Discussionsupporting
confidence: 91%
“…Lumbar puncture (LP) is an important procedure for the diagnosis and management of central nervous system (CNS) infections in children and adults, and refusal to this procedure is an issue that is encountered worldwide with a refusal rate as low as 5% in the United States to 24.7% in Malaysia, and even much higher refusal rates are observed in Iran and Kuwait of about 62% and 80%, respectively [1,2]. The refusal rate varies with the cultural beliefs of a population and their knowledge about the procedure [1][2][3][4]. A study by Ahmad et al including 215 patients with indications for LP, of which 70 (32.6%) families refused LP for their children, revealed that the most common reason for the parental refusal to LP was fear of limb paralysis (64.2%), followed by fear of death (31.3%), while in 19.4% of the cases, the parents considered the procedure unnecessary [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Khakshour et al, that examined 91 children admitted to Imam Reza Hospital in who underwent LP, 57.1% of the patients were male and 42.9% were female, which was consistent with the current study [ 7 ]. In the present study, most patients were in the age group of 8 weeks to 1 year (38.9%) and 1–3 years (25.5%).…”
Section: Discussionsupporting
confidence: 91%
“…This highlights the pivotal role of frontline clinicians in obtaining informed consent for the lumbar puncture as part of the routine diagnostic approach. Parental refusal to perform lumbar punctures in children with suspected central nervous system infection is common in low-middle income (LMIC) settings; a cross-sectional study of 215 families of Pakistani children who had indications for lumbar puncture showed that 33% refused [ 35 ]. Common reasons for refusal were lack of knowledge about the risks of the procedure (30%) and fear of paralysis of lower limbs (49%).…”
Section: Pillar 2: Diagnosis and Treatmentmentioning
confidence: 99%